Jokowi’s Speech on the 78th Indonesian Independence Day: A Critical Discourse Analysis - Butar Butar, Mei Lastri E.F. (Institut Agama Kristen Negeri Tarutung, 2023)
This study aims to analyze Jokowi’s speech on the 78th Indonesian Independence Day using the critical discourse analysis model developed by Norman Fairclough. A qualitative research design was employed in the conduct of this study. The data for this study were comprised of Jokowi’s speech on 78th Indonesia Independence Day. The analysis of Jokowi’s Independence Day speech employs linguistic choices, including pronouns for authority and community-building.. Discourse markers, English loanwords, and repetition enhance coherence and emphasis. Figurative language engages the audience emotionally and imaginatively. The discourse practice analysis reveals the speech's strategic delivery during a pivotal national event, emphasizing leadership, unity, economic growth, social development, and civil discourse. The social analysis uncovers insights into Indonesia's priorities through the inclusion of local culture, the political context, and the promotion of economic diversification and cultural heritage preservation. Jokowi deftly balances his authority as president with the importance of unity and public trust..